GENERIC STRUCTURE POTENTIAL OF THE ENGLISH INTRODUCTORY PAGES OF INSTITUTION WEBSITES IN VIETNAM - Tam, Nguyen Thi Minh (VNU Journal of Foreign Studies; Vol 34 No 6DO - 10.25073/2525-2445/vnufs.4324, 2018)
Nowadays, websites are an indispensible means for the purposes of information, administration and promotion. To address a variety of audience with different access purposes, of different age groups, and from different countries and background, websites are designed as a kind of multimodal text with the combination of language, signs, audio and visual components, and presentation effects. In such a globalization era, most websites are bilingual, trilingual, or even multi-lingual. In this paper, attempts are made to study the generic structure potential (GSP) of the English introductory information pages of institution websites in Vietnam. The GSP analysis is based on Hasan’s (1985) framework. The aim of the analysis is to explore the obligatory, the optional, and the iterative elements, which together construct the GSP of these websites. From the findings, suggestions related to improving the quality and the functioning of the websites could then be drawn out.